Intolerance of uncertainty prospectively predicts the transdiagnostic severity of emotional psychopathology: Evidence from a Veteran sample. (March 2022) - Hunt, Christopher; Exline, Julie J.; Fletcher, Terri L.; Teng, Ellen J.
Abstract: Intolerance of uncertainty (IU) has been conceptualized as a transdiagnostic vulnerability for emotional psychopathology, but few studies have tested whether it prospectively predicts emotional psychopathology, and none have utilized transdiagnostic and clinician-rated outcomes. To fill this gap, the present study tested whether IU prospectively predicted the clinician-rated severity of transdiagnostic emotional psychopathology six months later in a treatment-seeking Veteran sample. Participants completed the Intolerance of Uncertainty 12-item scale (IUS-12) and the Structured Clinical Interview for the DSM-5 (SCID-5) at Time 1 and again six-months later (Time 2); assessed emotional disorders included both anxiety-related disorders (i.e., post-traumatic stress disorder, generalized anxiety disorder, panic disorder, social anxiety disorder, obsessive compulsive disorder, specific phobia) and depressive conditions (i.e., major depressive disorder and persistent depressive disorder). Linear regression analyses revealed a bidirectional prospective relation between IU and emotional psychopathology, wherein higher Time 1 IUS-12 predicted greater Time 2 emotional disorder severity and greater Time 1 emotional disorder severity predicted higher Time 2 IUS-12. Follow-up analyses revealed that IU prospectively predicted the maintenance (but not the development) of anxiety-related issues, whereas prediction of Time 2 depression was nullified when controlling for Time 1 anxiety pathology. These findings implicate IU as a transdiagnostic vulnerability for emotional psychopathology and suggest the construct can be particularly useful as a treatment target and prognostic indicator for anxiety-related conditions. Highlights: Prospective relations between IU and emotional pathology were examined in Veterans. IU predicted more severe emotional pathology 6 months later. Prospective effects were similar across PTSD, depression, and non-PTSD anxiety. IU predicted the maintenance but not the development of anxiety pathology. Prospective effects on depression appeared due to comorbid anxiety.